Velocity and temperature distributions for mercury in turbulent flow - Louw, Robert Alexander (Department of Mechanical Engineering, 2016)
Velocity and temperature profiles in mercury are reported for vertical flow in a pipe at Reynolds numbers of approximately 3.3 x 10⁴ and 5.4 x 10⁴ with variation in heat flux. At a Reynolds number ≈ 3.3 x 10⁴ profiles are reported for thermal calming lengths of approximately 17, 36, 61 and 84. The velocity profiles, temperature profiles and Nusselt numbers are shown to be strongly influenced by free convection effects. Correlations are presented whereby the amount of distortion of the velocity profile from the isothermal profile under given conditions may be estimated, and the value of the Nusselt number under given conditions may be predicted.